2020
DOI: 10.1371/journal.pone.0229851
|View full text |Cite
|
Sign up to set email alerts
|

Empowering self-help groups for caregivers of children with disabilities in Kilifi, Kenya: Impacts and their underlying mechanisms

Abstract: Bringing up a child with disabilities in a low-income setting is challenged by inadequate resources, limited psycho-social support and poverty. Not surprisingly, many caregivers experience fatigue, distress and isolation. To address and investigate these issues, action was taken to set up twenty self-help groups focusing on caregiver empowerment. A realist evaluation design was adopted to evaluate impacts associated with the self-help process and to identify mechanisms determining the outcomes. Monthly monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 49 publications
0
14
0
1
Order By: Relevance
“…Literature on the continent of Africa (and globally) has identified a number of strategies for how families can be better supported. These include parent- caregiver- or family- advocacy and support groups, family income generation and poverty alleviation and community mobilisation (Aldersey, Turnbull, & Turnbull 2016 ; Bunning et al 2020 ; McConkey, Kahonde & McKenzie 2016 ; McKenzie & Chataika 2018 ). Studies, such as that by Marimbe et al ( 2016 ) in Zimbabwe examined needs for family caregivers of people with mental health issues and found that peer support groups provided families with opportunities to support one another and enhance coping abilities (Marimbe et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Literature on the continent of Africa (and globally) has identified a number of strategies for how families can be better supported. These include parent- caregiver- or family- advocacy and support groups, family income generation and poverty alleviation and community mobilisation (Aldersey, Turnbull, & Turnbull 2016 ; Bunning et al 2020 ; McConkey, Kahonde & McKenzie 2016 ; McKenzie & Chataika 2018 ). Studies, such as that by Marimbe et al ( 2016 ) in Zimbabwe examined needs for family caregivers of people with mental health issues and found that peer support groups provided families with opportunities to support one another and enhance coping abilities (Marimbe et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is an important element that could be strengthened within the future development of our programme. A study of self-help groups for caregivers of children with disabilities in Kenya also demonstrated that caregiver empowerment was associated not only with newly developed skills but also social connectedness and resource mobilisation (Bunning et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Home-grown approaches are developed bottom-up within the context in which they will be implemented or evaluated. Bunning and colleagues illustrate a novel combination of both approaches: the communication-focused intervention delivered to parents consisting of intervention approaches developed and used in HIC, such as objects of reference and intensive interaction (Bunning et al, 2014); and the caregiver empowerment groups responded to a locally identified need and were developed collaboratively within and for the target community (Bunning et al, 2020).…”
Section: Transported Vs Home-grown Approachesmentioning
confidence: 99%